Transmission electron microscopy in micro-nanoelectronics - Claverie, A. (Alain) (ISTE., 2013)
Today, the availability of bright and highly coherent electron sources and sensitive detectors has radically changed the type and quality of the information which can be obtained by transmission electron microscopy (TEM). TEMs are now present in large numbers not only in academia, but also in industrial research centers and fabs. This book presents in a simple and practical way the new quantitative techniques based on TEM which have recently been invented or developed to address most of the main challenging issues scientists and process engineers have to face.